Trifurcation of the right common carotid artery - R. Chitra (Indian Journal of Plastic Surgery)
Variations in the position of the bifurcation of the common carotid artery and the origin or branching pattern of the external carotid artery are well known and documented. Here, we report the trifurcation of the right common carotid artery in a male cadaver aged about 55 years. The right common carotid artery was found to divide into the external and internal carotids and the occipital artery. High division of bilateral common carotid arteries and a lateral position of the right external carotid artery at its origin were also observed in the same cadaver. There were two ascending pharyngeal arteries on the right side - one from the occipital artery and another from the internal carotid artery. The intraarterial approach is one of the most important routes for the administration of anticancer drugs for head and neck cancers. A profound knowledge of the anatomical characteristics and variations of the carotid artery such as its branching pattern and its position is essential to avoid complications with catheter insertion.